Види роду Prunus L. (Rosaceae Juss.) в Україні - Vasylyshyna, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The ecological and biological peculiarities and economy meaning species of genus Prunus L., which are spreaded in the nature and cultured in Ukraine, are given.